MAIN DIRECTIONS OF ENSURING SAFETY CONDITIONS IN TOURISM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines the main directions of security conditions in tourism. This work examines such issues as types of tourist problems, objects equipped with video surveillance cameras in Samarkand, indicators of safety of transport facilities, directions of information support in ensuring tourist security, main directions of investments in tourism security, as well as the creation of necessary conditions for the development of eco- and extreme tourism in the Samarkand region.